EFFECT OF LIGHT TRANSMITTING ABILITY OF FIBER POST ON BOND STRENGTH OF SELFADHESIVE RESIN CEMENT TO RADICULAR DENTINE - Siddiq, Adel Ahmed; Rayyan, Mohammad M; Ibrahim, Mohamed A.; Segaan, Lucette (European Scientific Journal, ESJ, 2015)
Aim: to investigate the effect of different light transmitting ability of two fiber posts systems on bond strength to the root canal dentine using dual cure self-adhesive resin cement. Materials and methods: 24 freshly extracted human premolars were decoronated and endodontically treated. Post spaces were prepared to a depth of 8 mm and width of 1.3 mm using manufacture’s supplied drills. Teeth were randomly classified into two main groups (n= 12) according to fiber post light transmission ability; group I; non-light transmitting fiber posts (NLT) (Reforpost, Angelus), group II; light transmitting fiber post (LT) (Exacto, Angelus). Both groups were cemented using self-adhesive resin cement (SpeedCEM, Ivoclar Vivadent). Using low speed saw (IsoMet, Buehler), a 2 mm thickness coronal, middle and apical sections were obtained from each sample. Then they were subjected to push out test using Instron machine (Lloyd Instruments Ltd) until failure. Data was collected and statistically analyzed. Results: the highest means in the coronal and middle parts was found, when using light transmitting fiber post, which scored (11.75, 10.30 MPa) compared with (6.51, 6.98 MPa) when using non-light transmitting group. One-way ANOVA among the groups revealed a significant difference between non-light and light transmitting fiber post. However, there is no significant difference on the middle and the coronal parts. Conclusions: There was no significant difference between non-light and light transmitting fiber post when all sections were added together. There is a reasonable doubt regarding the ability of light to reach more than 4 mm depth.